Pemberdayaan Masyarakat Melalui Pengolahan Sampah Organik Dan Anorganik Di Dusun Dasan Baru Desa Sukarara Kabupaten Lombok Tengah - Siti Yulianah M. Yusuf; Nindya Putri Syahida; Iswan; Nasruddin (AMMA : Jurnal Pengabdian Masyarakat, 2026)
The management of organic and inorganic waste remains a major challenge in many communities due to low levels of awareness and skill regarding waste handling. This community service initiative aims to enhance community knowledge, skills, and participation in waste management by applying the 3R principles (Reduce, Reuse, Recycle). The implementation methods included awareness-raising sessions, educational outreach, training, demonstrations, and hands-on guidance in processing organic waste into eco-enzymes and converting inorganic waste into products with economic value. The program targeted communities in villages or urban neighborhoods with the potential for developing community-based waste management systems. The results demonstrated an improved understanding of the importance of waste sorting at the source, enhanced skills in composting organic waste, and the ability to transform inorganic waste into marketable handicraft products. Beyond improving environmental cleanliness, the initiative created opportunities for increasing community income through the development of recycling-based enterprises. Thus, this community empowerment program—focused on organic and inorganic waste processing—has proven effective in fostering environmental awareness, reducing the volume of waste sent to landfills, and promoting the development of self-reliant, environmentally conscious communities.